The Practicality of Cognitive Conflict Digital Module (CCDM) in Electrical Materials for Students - Dwi Saputro Sigit; Rohmah Naelur; Admoko Setyo (SHS Web of Conferences)
Electrical matari requires reasoning skills to accelerate the understanding of concepts. The conflict cognitive strategy has proven to be effective in helping to understand the concept. This study aims to test the practicality of the Conflict Cognitive Digital Module (CCDM) as a learning medium on electrical materials applied in desktop applications. This research method uses descriptive quantitative techniques. The subjects of this study are 23 students of the informatics education study program. The research instrument used a practicality questionnaire with 3 indicators of application performance, ease of use of the application, and application display. The analysis of the questionnaire results through categorization not practical (0%-20%), less practical (21%-40%), quite practical (41%-60%), practical (61%-80%), adan very practical (81%-100%). The results of the research on application CCDM were the performance of the CCDM application is obtained with a percentage of 86% which is included in the very practical category. The ease of use of the CCDM application is 87% included in the very practical category. And the CCDM application display 88% is included in the very practical category. All statements of practicality were obtained 86% which were included in the very practical category. Suggestions for improvements add more types of music, built to mobile for easy learning anywhere.